The Effect of Tax Knowledge, Subjective Norms and Tax Sanctions on Individual Taxpayer Compliance with Tax Awareness as a Mediating Variable: A Study of MSME Entrepreneurs at Bengkulu Primary Tax Office - Rinda Yuwensi; Rini Indriani; Pratana Puspa Midiastuty (Journal of Accounting and Finance Management, 2026)
This study examines the effect of tax knowledge, subjective norms, and tax sanctions on the compliance of micro, small, and medium enterprise (MSME) individual taxpayers, with tax awareness acting as a mediating variable. Tax compliance among MSME taxpayers remains a major challenge for tax authorities, particularly in developing countries where voluntary compliance is essential for sustainable revenue collection. This research adopts a quantitative approach using survey data collected from 98 MSME individual taxpayers registered at the Bengkulu Dua Primary Tax Office, Indonesia. The sampling technique applied was convenience sampling, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that tax knowledge, subjective norms, and tax awareness have a positive and significant effect on taxpayer compliance. In contrast, tax sanctions do not have a direct significant effect on compliance. The mediation analysis reveals that tax awareness partially mediates the relationship between tax knowledge and subjective norms on taxpayer compliance, while fully mediating the effect of tax sanctions on compliance. These results highlight the importance of strengthening taxpayer awareness through education and social influence rather than relying solely on punitive measures to enhance MSME tax compliance.